(3GdJMGQjQ GdoefJNHI Ydi eJf GdWjHIs - (3EHQGgje Hf YGeQ Hf Ydj GdYHjOi GdeGdcjs; (3Ydj GdefUhQjs
(3ChdgG (B:s
(3GeG HYO ajbhd QGLj Yah QHg GdeHOA hGdeYjO GdabjQ EHQGgje GdYHjOj bO SCdfj HYV ENhGfj hNGUI NdGfj Cf CdNU JMQjQ GdYdGeI GdefUhQi s
(3BNQgG (B:s
(3aj BNQ cd ShQI Edi BNQ GdbQBf hGddg JYGdi CYde JeJ GdJMGQjQ HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1118s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs